Phytochemical and manufacturing profile of a sample of green tea formally sold in Lima, Peru - Moncada-Mapelli , Enrique (2024)
Green tea, derived from the Camellia sinensis plant, has been prized throughout history for its potential medicinal properties. It has been shown to contain polyphenols, such as flavones and flavonoids, which possess antioxidant properties and may benefit cardiovascular health and protect against neurological diseases. Chemical compounds in green tea are identified using qualitative and quantitative techniques. This descriptive and comparative study analyzed three green tea samples collected at a licensed shopping center in Lima, Peru. A qualitative method called phytochemical screening was used, which allowed identifying the presence of secondary metabolites such as flavonoids, alkaloids, phenols and tannins. Likewise, the results of the present research were compared to the results of green tea samples collected in Cusco (Peru) and Kano (Nigueria), referenced by previous studies using the same phytochemical screening method. The data are presented in descriptive tables. The main findings show a heterogeneous presence of tannins among the samples collected in Lima, and compared to the reference samples from Cuzco and Kano, possibly lower amount of flavonoids and phenols. Regarding manufacturing, it was found that two samples collected in Lima did not comply with the current regulations in the items of scientific name of the product, medicinal use of the product, and secondary metabolite reference. This study demonstrates heterogeneity in the phytochemical and manufacturing profile of the green tea samples collected in Lima, a situation that could be reflected in aspects of safety and efficacy for consumers. Therefore, further research on green tea for human consumption is needed to broadly understand the benefits versus risks due to the impact on human health.